PENYULUHAN KESEHATAN GIGI DAN MULUT DAN GERAKAN SIKAT GIGI YANG BAIK DAN BENAR DI SD NEGERI 17 KOTA BENGKULU - Syauqul Jannah; Devi Novia (CV. Kalimasada Group, 2026)
Dental health education for children is one of the efforts to instill an understanding in children that dental health is important. There are so many choices of health education methods to support good communication. The most commonly used conventional counseling method is lectures, which is a way of teaching through the presentation of facts and ideas orally, with or without media. Another educational method that is also effective and interesting for children is the storytelling method. This study was conducted to determine differences in the level of knowledge of dental and oral health after counseling using conventional methods and storytelling activities in grade 1 students at SD 17 Bengkulu. The total population of this study was 64 children. The results of the counseling conducted at SD 17 Bengkulu showed that grade 1 children still did not have sufficient knowledge about caring for their teeth and mouth, because children at SD 17 Bengkulu rarely received examinations and counseling about dental and oral health from the local health center.